2007
DOI: 10.1049/iet-smt:20060104
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic models of partial discharge activity in solid and liquid dielectrics

Abstract: A new model that can reproduce main stochastic features of partial discharge (PD) activity at AC and DC voltages was proposed. The type of PD activity because of microdischarges in small cavities present in dielectric materials was considered. Three different criteria were used to simulate an initiation of partial discharge inside voids. The simplest criterion of threshold type was used also to describe a decay of plasma in voids and subsequent decrease in conductivity to zero. After AC voltage was applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 28 publications
0
31
0
2
Order By: Relevance
“…They velocities of their expansion are from 100 m/s up to about 1 km/s. The simulation of the growth of gas cavities in the electric field was performed in [8]. It was shown that the growth dynamics and the development of the EHD flows are governed with the electric field acting on injected ions near the vapour-liquid interface.…”
Section: Simulation Of An Ion In Dense Dielectric Mediamentioning
confidence: 99%
“…They velocities of their expansion are from 100 m/s up to about 1 km/s. The simulation of the growth of gas cavities in the electric field was performed in [8]. It was shown that the growth dynamics and the development of the EHD flows are governed with the electric field acting on injected ions near the vapour-liquid interface.…”
Section: Simulation Of An Ion In Dense Dielectric Mediamentioning
confidence: 99%
“…Kupershtokh et al [18] recently improved the maximum ratio to be 10 7 by coupling a proper EOS with the Zhang-Chen approach [19]. The model is also applied in dielectric liquid discharge simulations [20].…”
Section: Introductionmentioning
confidence: 97%
“…Later, Hu et al [25] extended this method to general EOS. Moreover, some studies have shown that the exact difference method (EDM) force scheme [26] applied in Kupershtokh et al's work leads to error terms in the corresponding macroscopic equation, and thus the numerical problem being solved is 5 different from the original macroscopic problem [3,21]. Huang We here report a numerical error analysis of the Kupershtokh et al's model for EDM force scheme.…”
mentioning
confidence: 93%